Association between Physical Activity and Postnatal Depression - Abi Rafdi (HM Publisher, 2021)
Many changes could occur in a woman’s body, both mental and physical, during pregnancy and the postnatal period. The process of childbirth and a changing role as a new mom can be associated with many disturbances of emotions. Besides that, the development of baby blues or postpartum depression may occur in the puerperium period. Depression in post partum occurs in one month after childbirth and may be prolonged to one year. Depressive disorders in a young mother affect the mother and the newborn’s health status. That is why it is crucial to identify for factors that could significantly reduce the likelihood of developing depression in this period. The literature review was aimed at describing the relationship of physical activity during pregnancy and postpartum and the development of postnatal depression. It was shown that physical activity during pregnancy and puerperium, or in the postnatal period itself reduces the risk of developing depression in pregnancy and after delivery. Physical activity can be an essential factor in preventing depressive disorders in women in the postnatal period.